If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(x-1)=2(1-x)
We move all terms to the left:
2(x-1)-(2(1-x))=0
We add all the numbers together, and all the variables
2(x-1)-(2(-1x+1))=0
We multiply parentheses
2x-(2(-1x+1))-2=0
We calculate terms in parentheses: -(2(-1x+1)), so:We get rid of parentheses
2(-1x+1)
We multiply parentheses
-2x+2
Back to the equation:
-(-2x+2)
2x+2x-2-2=0
We add all the numbers together, and all the variables
4x-4=0
We move all terms containing x to the left, all other terms to the right
4x=4
x=4/4
x=1
| 108=12・n | | 4/3n+12=n | | 9-12r-99=-2r-4-12 | | 9x+7)=(10x-10) | | -11k-14=-12k-4 | | 6=s+6/4 | | -15/8=5x | | -4x+18=-4 | | -2v/5=6 | | 0.2x-0.8=2.8 | | 4z+8+5z+1+90=180 | | 7.1q-3.98=3.81+7.1q | | |2x|+6=24 | | -18+2y=1+2y | | x^2=11x=-28 | | 7(1+n)+8(3n-4)=68 | | 14s+20=1+17+16s | | 5.64+3.1w=12.15+1.91+3.1w | | 0,85(x+350)/3=x/2 | | 3(2x+2)+4=4x+22 | | 6/7x-15=69 | | 4v−3=4v+6−v | | f=1.8(46)+32 | | -6=0.7(r-12) | | 6/7x15=69 | | -10j−1−18=-19−10j | | 5x+2=5x−3 | | 15+0.25x=45+0.15x | | 7y+9=−7y−9 | | -7z+19=-20+6z | | 26x+5=28x-5 | | 3z=14+10 |